‫أثر‬‫الأنماط‬ ‫القيادية‬ ‫التسييرية‬في‬ الإبداع‬ الإداري‬ ‫دراسة‬‫حالة‬ ‫مؤسسة‬ ‫سونلغاز مديرية التوزيع سوق اهراس ‬ ‫‪-‬‬ ‫‪-‬‬ - ‬‫عقيلة ‫نهندي ‬ (My University, 2019)
The aim of this study is to tests the effect of leadership styles on innovation management within Sonelgaz Company - Distribution Department in Souk Ahras- through a descriptive and analytical approach. The questionnaire was adopted as a tool for collecting data by randomly distributing 30 questionnaires on the study sample from the frames employed , data were analyzed using SPSS statistical methods . The study reached several results, the most important of which are :  There is a significant effect of leadership management styles on innovation management of the employees in Sonelgaz Company - Distribution Department in Souk Ahras -.  There is a significant effect of democratic leadership in the activation and development of innovation management in Sonelgaz Company - Distribution Department in Souk Ahras -.  The results of the descriptive statistics for the analysis of the views of the sample of the study showed that the level of importance of the democratic leadership was high, which confirms the practice of leaders of the democratic model in the Sonelgaz Company - Distribution Department in Souk Ahras - Autocratic and Free leadership achieved an average level of importance.  The results of descriptive statistics to analyze the views of the sample of the study shows that the level of importance of innovation management was high, which confirms the availability of innovation management in Sonelgaz Company - Distribution Department in Souk Ahras -. This study recommended the need to continue to develop leadership practices that stimulate innovation management, such as empowering competent and experienced employees and encouraging them to take risks in performing new tasks and making decisions, working within one team and building good human relationship.